C‐MRC–based cooperative spatial modulation with antenna selection. (31st August 2020) - Aydin, Erdogan; Basar, Ertugrul; Ilhan, Haci; Kabaoğlu, Nihat
Summary: A new high‐performance low‐complexity cooperative maximal ratio combining (C‐MRC)‐based cooperative relaying scheme, which is called antenna selection‐aided cooperative spatial modulation scheme with C‐MRC (AS‐CSM), is proposed for decode and forward (DF)‐based cooperative relaying networks operating over independent but non‐identically distributed (i.n.d.) Rayleigh fading channels. The AS‐CSM scheme is formed with the combination of cooperative SM with the high‐performance low‐complexity coherent demodulator C‐MRC and antenna selection techniques. In the AS‐CSM scheme, the information is transmitted from the source terminal (ST) to the relay terminal (RT) and the destination terminal (DT) in the form of not only modulated symbols but also antenna indices, which carry additional information bits in the spatial domain. Therefore, a high spectral efficiency is obtained by the proposed scheme for cooperative relaying networks. In this scheme, first, the index of the activated antenna of ST is estimated, and the best antenna selection at RT is investigated considering the received instantaneous equivalent to signal‐to‐noise values acquired at DT. The transmitted symbols are estimated with low‐complexity coherent demodulator C‐MRC at DT by using the noisy signals from ST and RT. An exact closed‐form expression for the bit error probability (BEP) of the AS‐CSM scheme is derived, and the theoretical results are validated with Monte‐Carlo simulation results. Abstract : A new high‐performance low‐complexity cooperative maximal ratio combining (C‐MRC) based cooperative relaying scheme, which is called antenna selection‐aided cooperative spatial modulation scheme with C‐MRC (AS‐CSM), is proposed for decode and forward (DF)‐based cooperative relaying networks operating over independent but non‐identically distributed (i.n.d.) Rayleigh fading channels. The AS‐CSM scheme is formed with the combination of cooperative SM with the high‐performance low‐complexity coherent demodulator C‐MRC and antenna selection techniques.